Explaining fear of crime in Queensland - Carcach, Carlos (Journal of quantitative criminology, 1995)
A model to explain fear of crime in Queensland is developed and fitted to data from the 1991 Queensland Crime Victims Survey. Fear of crime is measured from the answers to the question about respondents' feelings of safety when walking alone in their area after dark. The results suggest that factors such as gender, age, poverty, educational level, labor force status, level of incivility in the area, perceived amount of crime in the area, and neighborhood cohesion all make an impact on fear of crime in a way that is consistent with the theory. The results also show that fear of crimein Queensland is explained by very concrete factors that can be subject to intervention and policy formulation by relevant bodies.